Making sense of public value: concepts, critiques and emergent meanings - Alford, John; O'Flynn, Janine (2009)
It has been two decades since the `public value' framework emerged, articulated initially at the Harvard Kennedy School. In this paper we set out the basics of the original approach, and then consider emerging critiques and meanings. Our aim is firstly to clarify the core concepts of Moore's approach, and secondly to track the new meanings of public value which are developing. This allows us to engage with the growing debate about public value both inside and outside academia, and also to discuss its trajectory as a new idea in public sector management. - Reproduced.
Keywords: Public administration